Preparation and characterisation of tough and porous polyvinyl alcohol/POC membrane for biomedical applications. Issue 4 (20th October 2022) - Niu, Zuoliang; You, Ziying; Lu, William W.; Wang, Zhenming; Wang, Chenglin
Abstract: Polyvinyl alcohol (PVA) is a synthetic polymer that has been extensively studied for fabricating porous membranes via electrospinning for diverse biomedical applications. However, the poor mechanical properties of electrostatically spun PVA nanofiber membranes severely limit their application in the biomedical field. Therefore, porous, tough hybrid PVA‐based fibrous membranes were prepared by introducing poly (1, 8‐octanediol citrate) (POC) into PVA fibrous membranes followed by sodium citrate treatment. The tensile modulus, fracture strength, and fracture toughness of the sodium citrate‐treated PVA/POC (CPP) membranes achieve 119.81 ± 5.32 MPa, 10.34 ± 1.57 MPa and 401.51 ± 11.67 MJ m −2, respectively, which were ∼60, ∼10, and ∼4 times higher than those achieved by the pristine PVA membrane. Moreover, the novel CPP membranes exhibited suitable biodegradation ratios and high cell/issue affinities, suggesting their potential biomedical applications in soft or hard tissue repair. This strategy, which provides porous structures, high mechanical properties and excellent biocompatibility, demonstrates a facile but effective approach for the development of advanced biomaterials.